Description of JKN Patient Satisfaction with the Quality of Dental Health Services in Hospitals - Betan, Abubakar; Musiana, Musiana; Wisma Sari, Sinta; Efendi, Efendi; Badaruddin, Badaruddin; Fredy Saputra, M. Khalid; Arfah, Andi (International Journal of Health Sciences, 2023)
The National Health Insurance (JKN) with a pre-payment financing system, which uses a capitation system for primary health services including dental and oral health services. The implementation of JKN also requires increased access and quality of health services, both at the First Level Health Facility and Advanced Health Facilities. The implementation of JKN requires support from promotive and preventive public health efforts so that the community remains healthy and does not get sick easily, and is useful in helping to control the burden of the necessary state budget. First-level health facilities that play a role in providing promotive and preventive health services are important, one of which is the Community Health Center or Puskesmas. The purpose of this study was to determine the description of JKN patient satisfaction with the quality of dental health services. The type of research used is a literature study with the method of collecting library data, reading and recording, and processing materials. The data used comes from textbooks, journals, scientific articles, literature reviews which contain an overview of JKN Patient Satisfaction with the Quality of Dental Health Services at the Hospital. National Health Insurance patient satisfaction in receiving this service is divided based on 5 SERVQUAL dimensions, namely tangibility, reliability, assurance, responsiveness and four. The quality of health services is health services that can satisfy every user of health services in accordance with the average satisfaction level of the population and its implementation in accordance with professional standards and ethical codes. Conclusion: The level of patient satisfaction with health services based on reliability (Reliability), responsiveness (Responsivines), Assurance (Assurance), direct evidence (Tangiable), human relations (Empaty) is a very satisfied category.